2018
DOI: 10.3389/fimmu.2018.01090
|View full text |Cite
|
Sign up to set email alerts
|

The CXC Chemokine Receptor 3 Inhibits Autoimmune Cholangitis via CD8+ T Cells but Promotes Colitis via CD4+ T Cells

Abstract: CXC chemokine receptor 3 (CXCR3), a receptor for the C-X-C motif chemokines (CXCL) CXCL9, CXCL10, and CXCL11, which not only plays a role in chemotaxis but also regulates differentiation and development of memory and effector T cell populations. Herein, we explored the function of CXCR3 in the modulation of different organ-specific autoimmune diseases in interleukin (IL)-2 receptor deficiency (CD25−/−) mice, a murine model for both cholangitis and colitis. We observed higher levels of CXCL9 and CXCL10 in the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…In addition, we observed that CXCL13 , as the ligand of terminal Tex cells, interacted with CXCR3 as the receptor of pre-exhausted T cells. CXCR3 , as a co-receptor for the chemokine CXCL13 , is chemotactic and involved in regulating the differentiation and development of memory cells and effector T cells ( 31 ). This indicates that cellular communication of terminal Tex cells with pre-exhausted T cells might lead to differentiation toward exhaustion.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we observed that CXCL13 , as the ligand of terminal Tex cells, interacted with CXCR3 as the receptor of pre-exhausted T cells. CXCR3 , as a co-receptor for the chemokine CXCL13 , is chemotactic and involved in regulating the differentiation and development of memory cells and effector T cells ( 31 ). This indicates that cellular communication of terminal Tex cells with pre-exhausted T cells might lead to differentiation toward exhaustion.…”
Section: Discussionmentioning
confidence: 99%
“…The axes of IFN-g:CXCL10:CXCR3 and CCL4:CCR5 are thus likely to recruit gluten-specific CD4 + T cells into the celiac lesion. Although disease-specific cells have not been demonstrated in most other autoimmune diseases, increased numbers of CCR5 + , CXCR3 + , CD4 + T cells or increased levels of their receptor ligands have been reported in patient cohorts with different autoimmune conditions, including T1D [57], MS [58,59], RA [60,61], SLE [62], Ssc [63], psoriasis [64,65], and in several murine autoimmune models [66,67].…”
Section: Blocking Infiltration To the Inflammatory Tissuementioning
confidence: 99%
“…This study identified a direct role of the CXCL9-CXCR3 axis in aiming the excess tissue recruitment of T cells in the Gba1 9V/− mouse. CXCR3 is an attractive therapeutic target for treating T cell-mediated inflammatory diseases [ 83 , 84 , 90 , 91 , 92 , 93 , 94 , 95 , 96 ]. CXCL9-mediated ex vivo and in vivo chemotaxis of T cell subsets (i.e., CD4 + T and CD8 + T cells) in the presence or absence of mouse anti-CXCR3 antibodies showed that targeting CXCR3 caused marked reduction in CXCL9-mediated enhanced tissue recruitment of T cell subsets in GD.…”
Section: Discussionmentioning
confidence: 99%